ENGLISH IN THE COMMUNICATION FIELD OF UKRAINIANS AS A NEED FOR THE TRAINING OF THE NEW GENERATION OF TEACHERS - Rozman, Iryna; Achilova, Valeriya (Mountain School of Ukrainian Carpaty, 2023)
The article substantiates the necessity of training new generation teachers for the effective introduction of the English language into the communicative field of Ukrainians. The significance and importance of the English language as a language of international communication and its influence in the context of the language policy of the world are proved. A number of studies were singled out, which proved that as early as September 2013, the Ministry of Education and Science of Ukraine and the British Council launched the "New Generation School Teacher" initiative in response to an urgent need in Ukrainian education: reforming both the content and the methodology of the traditional approach to student training, who study abroad. teachers of language schools of Ukrainian higher educational institutions. Focused attention on the need to present the English language with the status of mandatory for government employees, updating teaching in comprehensive secondary education institutions and institutions of higher education. The forecast of scientific intelligence regarding the future teaching of the English language is highlighted. In addition, the level of English proficiency of Ukrainians as of January 2023 is illustrated. The main ways of training new generation teachers for self-development and, at the same time, implementation of achievements in the educational process are described. Using sociological data, a clear relationship between the European and Ukrainian education systems was traced. It has been proven that knowledge of foreign languages is the key to success in today's world, where intercultural communication and processing of huge amounts of information is gaining more and more importance Emphasis is placed on the need to implement the development of planned professional development and educational projects aimed at taking into account European trends in the field of modern philological science. It is noted on the perspective and needs of reforming modern Ukrainian education. The communicative strategies of the English language in the context of professional training of the future specialist are determined. The authors of the article prove the urgency of the process of increasing the level of English language competence of Ukrainians. It is emphasized that teachers of the 21st century provide the role of a teacher who constantly helps people to work together more effectively, focus on the quality of knowledge of the acquirers, develop thinking skills of creative, effective communication and cooperation in a team. It is noted that modern students, as a new generation of teachers, need to take the work of using the portfolio as a system (it can be supplemented throughout life). The method of training English language teachers includes the main principles of the training program, modules and their characteristics, evaluation criteria and sample tasks, sample materials and a glossary. Professional development takes place during the understanding of the peculiarities of practical training, understanding of education by trainee students. It is emphasized that the most important aspect for foreign language teachers is the communicative method of teaching and learning the language.